Spectral reflectance of whale skin above the sea surface: a proposed measurement protocol. Issue 3 (10th March 2020) - Cubaynes, Hannah C.; Rees, W. Gareth; Jackson, Jennifer A.; Moore, Michael; Sformo, Todd L.; McLellan, William A.; Niemeyer, Misty E.; George, John C.; van der Hoop, Julie; Forcada, Jaume; Trathan, Phil; Fretwell, Peter T.
Abstract: Great whales have been detected using very‐high‐resolution satellite imagery, suggesting this technology could be used to monitor whales in remote areas. However, the application of this method to whale studies is at an early developmental stage and several technical factors need to be addressed, including capacity for species differentiation and the maximum depth of detection in the water column. Both require knowledge of the spectral reflectance of the various whale species just above the sea surface, as when whales bodies break the surface of the water to breath, log or breach, there is, at times, no sea water between the whale's skin and the satellite sensor. Here we tested whether such reflectance could be measured on dead whale tissue. We measured the spectral reflectance of fresh integument collected during the bowhead subsistence harvest, and of thawed integument samples from various species obtained following strandings and stored at −20°C. We show that fresh and thawed samples of whale integument have different spectral properties. The reflectance of fresh samples was higher than the reflectance of thawed samples, as integument appears to darken after death and with time, even under frozen conditions. In this study, we present the first whale reflectance estimates (without the influence of sea water and for dead tissue). These provide a baseline for additional work, needed to advance the use of satellite imagery to monitor whales and facilitate their conservation. Abstract : To help further develop the use of very‐high‐resolution satellite imagery to study whales, the reflectance of the various species of whales above the sea surface is required. Here we tested the feasibility of measuring the reflectance of thawed whale integuments as an alternative to measuring it on live whales. We found that post‐mortem samples darken soon after death and the longer they are kept in a freezer.